Unconventional two-dimensional germanium dichalcogenides. Issue 16 (11th April 2018) - Wang, Jiangjing; Ronneberger, Ider; Zhou, Ling; Lu, Lu; Deringer, Volker L.; Zhang, Baiyu; Tian, Lin; Du, Hongchu; Jia, Chunlin; Qian, Xiaofeng; Wuttig, Matthias; Mazzarello, Riccardo; et al.
Abstract : A novel 2D phase of germanium dichalcogenides (GeTe2 ) is achieved by engineering the composition of a GeSbTe heterostructure. Abstract : The recently discovered two-dimensional (2D) group IV chalcogenides attract much attention owing to their novel electronic and photonic properties. All the reported materials of this class favor (distorted) octahedral coordination via p bonding; by contrast, in the dichalcogenides where the bonding tendency approaches sp 3, no corresponding 2D phase has been realized so far. Here, by engineering the composition of a chalcogenide heterostructure, the hitherto elusive GeTe2 is experimentally observed in a confined 2D environment. Density functional theory simulations predict the existence of a freestanding monolayer of octahedrally coordinated GeTe2 under tensile strain, and the existence of GeSe2 and GeS2 in the same form under equilibrium conditions. These 2D germanium dichalcogenides are either metallic or narrow gap semiconducting, and may lead to new applications in nanoscale electronics.